On monomorphic topological functors with finite supports - Banakh, T.O.; Martynenko, M.V.; Zarichnyi, M.M. (Carpathian Mathematical Publications, 2012)
We prove that a monomorphic functor F:Comp→Comp with finite supports is epimorphic, continuous, and its maximal -modification F^° preserves intersections. This implies that a monomorphic functor F:Comp→Comp of finite degree Fn preserves (finite-dimensional) compact ANRs if the spaces F, F^° and Fn are finite-dimensional ANRs. This improves a known result of Basmanov.